1999
DOI: 10.1530/jrf.0.1170041
|View full text |Cite
|
Sign up to set email alerts
|

Influence of protein supplements on the secretion of leukaemia inhibitory factor by mitomycin-pretreated Vero cells: possible application to the in vitro production of bovine blastocysts with high cryotolerance

Abstract: A co-culture system for bovine embryos using mitomycin-treated Vero cells and serum\x=req-\ supplemented modified synthetic oviduct fluid (mSOF) supports the development of in vitro maturation and fertilization-derived oocytes to hatched blastocysts. In this system, it has been suggested that one contribution made by the co-culture cells to embryo development is production of the cytokine leukaemia inhibitory factor (LIF). However, there are concerns about exposure of early embryos to serum due to its incompat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 3 publications
1
8
0
1
Order By: Relevance
“…In the present experiment, there was no significant increase in cleavage and morula production rate when the presumptive zygotes were cultured in LIF media, but a significantly improved blastocyst production and hatching rate was observed when compared with the control group. Similar results were reported by Carnegie et al (1999) while using high LIF secreting coculture system for bovine embryo production, which Figure Y Phylogenetic relationship of the leukaemia inhibitory factor (LIF) nucleotide sequences from different species using DNASTAR Version 4.0, Inc., USA following the alignment of the partial ORF sequences using ClustalW method (nucleotide p distance). resulted in improvement of blastocyst formation and also in a better pregnancy rate after transfer of cryopreserved embryos into recipient cows.…”
Section: Discussionsupporting
confidence: 77%
“…In the present experiment, there was no significant increase in cleavage and morula production rate when the presumptive zygotes were cultured in LIF media, but a significantly improved blastocyst production and hatching rate was observed when compared with the control group. Similar results were reported by Carnegie et al (1999) while using high LIF secreting coculture system for bovine embryo production, which Figure Y Phylogenetic relationship of the leukaemia inhibitory factor (LIF) nucleotide sequences from different species using DNASTAR Version 4.0, Inc., USA following the alignment of the partial ORF sequences using ClustalW method (nucleotide p distance). resulted in improvement of blastocyst formation and also in a better pregnancy rate after transfer of cryopreserved embryos into recipient cows.…”
Section: Discussionsupporting
confidence: 77%
“…Vero cell secretions include the growth factors PDGF, IL-6 and LIF [31], all of which are also found in the reproductive tract [36][37][38][39]. An interesting study by Carnegie et al suggests that in vitro production of blastocysts with high cryotolerance can be modulated by levels of LIF secretion by Vero cells [40].…”
Section: Discussionmentioning
confidence: 99%
“…When the maturation of bovine oocytes was stimulated, the development of embryos accelerated and their morphological quality was improved, which resulted in a higher yield of embryos suitable for cryopreservation (de Matos et al, 1996;Mtango et al, 2003). Culture conditions have been shown to be a very important factor for survival of embryos after cryopreservation (Carnegie et al,1999;Hochi et al, 1999;Otoi et al, 2000;Cho et al, 2002;Abe and Hoschi 2003;Galli et al, 2003;. It could be shown that, that it is possible to obtain more developed embryos of higher morphological quality that were more resistant to the cryopreservation procedure by modification of the culture condition.…”
mentioning
confidence: 99%